Gambaran Kualitas Lingkungan Sungai Cimandiri Akibat Cemaran Merkuri di Wilayah Penambangan Emas Skala Kecil (PESK) Kabupaten Sukabumi - Izza Hananingtyas (Biotropic : The Journal of Tropical Biology, 2023)
In Indonesia, ASGM has increased. This results in an increased risk of mercury pollution in the environment (Minamata Initial Assessment Report, 2019).  The amalgamation process for ASGM in Sukabumi, it used mercury as basic material for amalgamation process. It can increase to negative impacts on the environment and humans. This study aims to describe the impact of mercury contamination on the environmental quality of the Cimandiri River around ASGM in Sukabumi District. This research was conducted using a laboratory test method with reference to PP No. 22 at 2021 and SNI 7387 at   2009. The results of the tests found that the highest mercury exposure occurred in aquatic biota (catfish, snakehead and eel) which exceeded the quality standard, although the media water and sediment does not exceed the quality standard. This indicates that the quality of the Cimandiri River is unsafe for biota due to mercury contamination in local biota around ASGM. Therefore, there is a need for further studies on the safety of local food products from the Cimandiri River.